Sub chronic toxicity study of mixed fungal isolates culture filtrates from ground nut hay in rats (Journal of Laboratory Animal Science, 2019)
Sub chronic toxicity study of mixed culture filtrate of Rhizopus oryzae, Fusarium verticilloides and Fusarium xylarioides isolated from the fungal contaminated ground nut hay was conducted in rats. The fungi were isolated from the contaminated  groundnut hay which caused mycotoxicosis in cross bred cattle, exhibited the clinical signs of colic, tenesmus, ruminal  atony, anorexia, bleeding from nostrils, rectum and fly bite site. The rats were gavaged with culture filtrate at the dose level  of 0.5, 1 and 2 ml daily for 90 days. Clinical signs observed were diarrhea, weakness, severe arching of back, swollen  forehead and conjunctival hemorrhage. Cutaneous hemorrhagic patches on back, scrotum, abdomen, ears and legs region  seen. There was a significant increase (P
Keywords: Culture filtrate; sub chronic toxicity; groundnut hay; rat